Interactions Between ABCB1 Genotype and Preoperative Statin Use Impact Clinical Outcomes Among Breast Cancer Patients - Tryggvadottir, Helga; Huzell, Louise; Gustbée, Emma; Simonsson, Maria; Markkula, Andrea; Jirström, Karin; Rose, Carsten; Ingvar, Christian; Borgquist, Signe; Jernström, Helena (Frontiers in Oncology, 2018)
Multiple clinical trials investigate statins’ effects in breast cancer. The ABCB1 genotype appears to influence statin response and toxicity in the cardiovascular setting. This exploratory study aimed to investigate the interplay between preoperative statin use, ABCB1 genotype, and tumor-specific expression of the statin target 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) in breast cancer. Preoperative statin use, ABCB1 C3435T genotype, and HMGCR expression in relation to outcome were analyzed in 985 primary breast cancer patients from a population-based prospective cohort in Sweden from 2002-2012. Preoperative statin use (n=80) was not associated with ABCB1 C3435T genotype (n=576), HMGCR expression (n=848), or clinical outcomes. ABCB1 C3435T TT-carriers had lower risk of breast cancer events than any C-carriers (adjusted hazard ratio (HRadj) 0.74; 95%CI 0.49, 1.12), but only in non-statin users (Pinteraction=0.042). Statin users with TT genotype had higher risk of distant metastasis (HRadj 4.37; 95%CI 1.20, 15.91; Pinteraction=0.009) and shorter overall survival than other patients (HRadj 3.77; 95%CI 1.37, 10.39; Pinteraction=0.019). In conclusion, there were nominally significant interactions between ABCB1 genotype and preoperative statin use on clinical outcomes, while preoperative statin use was not associated with outcomes. Since this is an exploratory study of the impact of the ABCB1 genotype in relation to statin use and clinical outcomes in the breast cancer setting, the results should be interpreted with caution and warrant replication in an independent cohort, preferably in a randomized setting. Since statin use is common in breast cancer patients, it would be of interest to further elucidate the clinical impact of the ABCB1 genotype in breast cancer.